Corrosion behavior of 2507 duplex stainless steel in simulated SO2-Polluted seawater - ZHU Min; ZHU Tao; CHEN Ming; GUO Shao-yi; YUAN Yong-feng; YU Gao-hong; NIE Lun (工程科学学报)
The corrosion behavior of 2507 duplex stainless steel in simulated seawater containing different concentrations of NaHSO3 solution was investigated using open circuit potential, electrochemical impedance spectroscopy (EIS), Mott-Schottky curves, and an immersion corrosion test. The results depict that the open circuit potential shifts negatively with an increase in the concentration of NaHSO3, whereas the corrosion tendency of the steel increases. The charge transfer resistance (Rt) decreases with the increased concentration of NaHSO3, which suggests that the corrosion resistance is reduced. The corroded stainless steel exhibits localized pitting corrosion. Further, the degree of corrosion as well as the corrosion rate increases with an increase in the concentration of NaHSO3. The results that are obtained using the Mott-Schottky curves and EIS test depict that the addition of NaHSO3 increases the concentration of point defects on the passive surface film of 2507 stainless steel, reducing its stability and decreasing its charge transfer resistance, resulting in an increased probability of corrosion. This may be caused due to the fact that the addition of NaHSO3 increases the acidity of the solution, which accelerates the damage that is caused to the passive film on the stainless steel.